Footwear modification following hallux valgus surgery: The all-or-none phenomenon - Robinson, Cal (World J Methodol, 2016)
AIM: To define footwear outcomes following hallux valgus surgery, focusing on patient return to comfortable and heeled footwear and patterns of post-operative footwear selection. METHODS: Surgical intervention is indicated for symptomatic cases of hallux valgus unresponsive to conservative methods, with favourable reported outcomes. The return to various types of footwear post-operatively is reflective of the degree of correction achieved, and corresponds to patient satisfaction. Patients are expected to return to comfortable footwear post-operatively without significant residual symptoms. Many female patients will additionally attempt to return to high-heeled, narrow toe box shoes. However, minimal evidence exists to guide their expectations. Sixty-five female hallux valgus patients that had undergone primary surgery between 2011 and 2013 were retrospectively identified using our hospital surgical database. Patients were reviewed using a footwear-specific outcome questionnaire at a mean 18.5 mo follow-up. RESULTS: Eighty-six percent of patients were able to return to comfortable footwear post-operatively with minimal discomfort. Of those intending to resume wearing heeled footwear, 62% were able to do so, with 77% of these patients wearing these as or more frequently than pre-operatively. No significant difference was observed between pre- and post-operative heel size. Mean time to return to heeled footwear was 21.4 wk post-operation. Cosmetic outcomes were very high and did not adversely impact footwear selection. CONCLUSION: We report high rates of return to both comfortable and heeled shoes in female patients following primary hallux valgus surgery. We observed an “all-or-none phenomenon” where patients rejected a return to heeled footwear unless able to tolerate them at the same frequency and heel size as pre-operatively. A minority of patients were unable to return to comfortable footwear post-operatively, which had adverse ramifications on their quality-of-life. We recommend that the importance of managing patient expectations through appropriate pre-operative counselling be emphasized in forefoot surgery.